White too long : the legacy of white supremacy in American Christianity - Jones, Robert P. (Robert Patrick) (Simon & Schuster, 2020)
"WHITE TOO LONG draws on history, statistics, and memoir to urge that white Christians reckon with the racism of the past and the amnesia of the present to restore a Christian identity free of the taint of white supremacy"--